A Miocene tetraconodontine (Suidae, Mammalia) from Falkenberg (Halland, Sweden). (2nd January 2019) - Mörs, Thomas; Liu, Liping; Hagström, Jonas
ABSTRACT: An isolated suid molar from Falkenberg in Halland, Sweden, is attributed to the extinct Miocene subfamily Tetraconodontinae based on general tooth morphology. The m3 is high-crowned and possesses a shorter talonid than other European tetraconodontines, judging from those species where the m3 is known. The most unusual feature is the highly lifted hypoconulid. Due to these specific dental features, it is not possible to assign the tooth to any known tetraconodontine species, but the material is also insufficient to create a new species. Based on the tooth dimensions, the Falkenberg suid was of the size of a peccary. The biostratigraphic range of Tetraconodontinae in Europe is 15–10 Ma, which implies an Early to Late Miocene age for the tooth. As no Miocene deposits are found in Sweden, the specimen was probably transported from the nearest source area in Southern Jutland, Denmark, by ice rafting. The Falkenberg tooth represents one of the northernmost records of European Miocene land mammals.